Driving Pressure Is a Risk Factor for ARDS in Mechanically Ventilated Subjects Without ARDS. - Roca, Oriol; Peñuelas, Oscar; Muriel, Alfonso; García-de-Acilu, Marina; Laborda, César; Sacanell, Judit; Riera, Jordi; Raymondos, Konstantinos; Bin Du; Thille, Arnaud W.; Ríos, Fernando; González, Marco; et al. (Respiratory Care, 2021)
BACKGROUND: Driving pressure (DP) has been described as a risk factor for mortality in patients with ARDS. However, the role of DP in the outcome of patients without ARDS and on mechanical ventilation has received less attention. Our objective was to evaluate the association between DP on the first day of mechanical ventilation with the development of ARDS. METHODS: This was a post hoc analysis of a multicenter, prospective, observational, international study that included subjects who were on mechanical ventilation for > 12 h. Our objective was to evaluate the association between DP on the first day of mechanical ventilation with the development of ARDS. To assess the effect of DP, a logistic regression analysis was performed when adjusting for other potential risk factors. Validation of the results obtained was performed by using a bootstrap method and by repeating the same analyses at day 2. RESULTS: A total of 1,575 subjects were included, of whom 65 (4.1%) developed ARDS. The DP was independently associated with ARDS (odds ratio [OR] 1.12, 95% CI 1.07-1.18 for each cm H2O of DP increase, P < .001). The same results were observed at day 2 (OR 1.14, 95% CI 1.07-1.21; P < .001) and after bootstrap validation (OR 1.13, 95% CI 1.04-1.22; P < .001). When taking the prevalence of ARDS in the lowest quartile of DP (≤9 cm H2O) as a reference, the subjects with DP > 12-15 cm H2O and those with DP > 15 cm H2O presented a higher probability of ARDS (OR 3.65, 95% CI 1.32-10.04 [P 5 .01] and OR 7.31, 95% CI, 2.89-18.50 [P < .001], respectively). CONCLUSIONS: In the subjects without ARDS, a higher level of DP on the first day of mechanical ventilation was associated with later development of ARDS. (ClinicalTrials.gov registration NCT02731898.)